Clinical Profile of TB Patients on DOTS at a Tertiary Care Hospital (Academia Journal of Medicine, 2024)
Background: Tuberculosis was considered to be among the top ten causes of global mortality and morbidity. The highest incidence of TB was found in developing countries. Estimates suggest that 32% of the world‟s population was infected with TB. In India, it was seen that TB kills  more adults than any other infectious disease. 20% global burden of TB was in India. Subjects and Methods: Before initiating anti tuberculosis treatment a detailed clinical assessment which included history and clinical examination was done. Hematological investigations  like HIV test is done as per ICTC along with HBsAg. Hematological investigations included hemoglobin, WBC count, differential count,  platelet count, prothrombin time and ESR. Biochemical investigations included total bilirubin, direct bilirubin, AST, ALT, alkaline  phosphatase, random blood sugar, blood urea, s.creatinine and uric acid. Results: Out of the 50 patients studied, 70 % patients were sputum  positive and 30 % were sputum negative. This is probably because majority of the patients studied were pulmonary tuberculosis. Conclusion:  Adverse drug reaction was seen in 29 patients (58 %). One or more types of ADR was seen in these patients.
Keywords: TB patients; DOTS; HIV